139k views
0 votes
Ss below.
help would be appreciated.

Ss below. help would be appreciated.-example-1

1 Answer

4 votes

Answer:

(3,0,0)

Explanation:

3x + 5y + z = 9 --------------(I)

-4y - z = 0 -------------------(II)

z = -4y

2x + 3y - 4z = 6 (III)

Substitute z = -4y in equation (I) and (III)

3x +5y - 4y = 9

3x + y = 9 -----------------------(a)

2x + 3y - 4*(-4y) = 6

2x + 3y + 16y = 6

2x + 19y = 6 -------------------(b)

Multiply equation (a) by (-19) and then add. So, y will be eliminated and we can get the value of x

(a)*(-19) -57x - 19y = -171

(b) 2x + 19y = 6

-55x = -165

x = -165/-55

x = 3

Plugin x = 3 in equation (a)

3*3 + y = 9

9 + y = 9

y = 9 - 9

y = 0

Plug in y = 0 in equation (II)

-4*0 - z = 0

z = 0

User Samya
by
5.7k points